A new tube chamber system for evaluation of anterior chamber pressure during phacoemulsification tested in porcine eyes - Fumiaki Higashijima; Makoto Hatano; Manami Ohta; Tadahiko Ogata; Takuya Yoshimoto; Atsushige Ashimori; Makiko Wakuta; Kazuhiro Kimura (International Journal of Ophthalmology)
AIM: To measure the optimal anterior chamber pressure (ACP) for safe phacoemulsification using a new tube chamber system with internal pressure measurement function in the porcine eye. METHODS: The 20-gauge and 21-gauge straight tips with yellow and orange sleeves, respectively, were covered by a test chamber combined with a pressure sensor for measuring ACP. This was measured for 20s from 10s after starting aspiration in the linear mode using vacuum levels of 200 and 150 mm Hg with a 20-gauge tip, and 300 and 250 mm Hg with a 21-gauge tip. Using a porcine eye, a pressure sensor fixed with a 0.9 mm corneal incision measured ACP. For the posterior capsule contact assay, porcine eyes were treated as described above, and the ultrasonic needle tip was held at the height of the iris and aspirated for 30s in linear mode at a vacuum of 200 and 150 mm Hg for the 20-gauge tip, and 300 and 250 mm Hg for the 21-gauge tip. The bottle height at which the posterior capsule accidentally contacted the ultrasonic tip was recorded, and the estimated ACP was calculated. RESULTS: The internal pressure of the new tube chamber system and ACP from the porcine eye closely matched proportional changes at vacuum levels of 200 and 150 mm Hg with 20-gauge tips. Similarly, proportional changes at vacuum levels of 300 and 250 mm Hg with the 21-gauge tip were nearly equal. The bottle height at which the posterior capsule contacted with the tip and estimated ACP were 57.5±12.6 cm (20.2±7.9 mm Hg) at 200 mm Hg with a 20-gauge tip, 35.0±10.0 cm (16.6±6.3 mm Hg) at 150 mm Hg with a 20-gauge tip, 47.5±12.6 cm (18.7±8.7 mm Hg) at 300 mm Hg with a 21-gauge tip, and 32.5±5.0 cm (15.7±3.5 mm Hg) at 250 mm Hg with a 21-gauge tip. CONCLUSION: A comprehensive understanding of this chamber system's characteristics and usage can resolve anterior chamber instability caused by changing preoperative settings on the phaco machine.